2009
DOI: 10.1007/s11258-009-9574-7
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf shrubs are stronger competitors than graminoid species at high nutrient supply in peat bogs

Abstract: Climate warming is likely to increase nutrient mineralization rates in bog ecosystems which may change the plant species composition. We examined the competitive relationships between two graminoid species, Eriophorum vaginatum and Rhynchospora alba, and two ericoid species, Calluna vulgaris and Vaccinium oxycoccus, at different nutrient supply rates. In a greenhouse, the plants were grown in monocultures and mixtures at four nutrient treatments: control, high N, high P, and high N ? P. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…Contrary to short-term experimental studies (Aerts et al 1992;Berendse et al 2001;Wiedermann et al 2007;Kool & Heijmans 2009;Breeuwer et al 2010), we have not found any statistically significant change in total cover of dwarf shrubs, even if frequency of some dwarf shrub species such as Calluna vulgaris, Vaccinium myrtillus and Oxycoccus palustris agg. (in the Hrubý Jeseník Mountains) and Empetrum nigrum (in the Jizerské hory Mountains) changed.…”
Section: Changes In Particular Species Frequencies and The Possible Rcontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to short-term experimental studies (Aerts et al 1992;Berendse et al 2001;Wiedermann et al 2007;Kool & Heijmans 2009;Breeuwer et al 2010), we have not found any statistically significant change in total cover of dwarf shrubs, even if frequency of some dwarf shrub species such as Calluna vulgaris, Vaccinium myrtillus and Oxycoccus palustris agg. (in the Hrubý Jeseník Mountains) and Empetrum nigrum (in the Jizerské hory Mountains) changed.…”
Section: Changes In Particular Species Frequencies and The Possible Rcontrasting
confidence: 99%
“…Growth of Sphagnum species is supported by increasing CO 2 concentrations (Mitchell et al 2002) and a high water level ), but vascular plants benefit from increasing temperature (Weltzin et al 2000;Gunnarsson et al 2004) and a water level decline (Bragazza 2006a;Gerdol et al 2008). Further, N addition enhances biomass of vascular plants, especially ericoid dwarf shrubs (Kool & Heijmans 2009;Breeuwer et al 2010), which produce more easily decomposable litter than bryophytes Heijmans et al 2001) and compete asymmetrically with Sphagna for light (Malmer et al 2003;Bubier et al 2007). A slightly increased N concentration enhances Sphagnum production, whereas a strongly increased N concentration reduces Sphagnum production through vascular plant competition (Gunnarsson & Rydin 2000;Berendse et al 2001;Gerdol et al 2007).…”
mentioning
confidence: 99%
“…Many studies have shown that environmental conditions can change inter-specific interactions [3], [4], [6], [18], [34]–[36]. Our study also showed that nitrogen level changed the interactions between the two species.…”
Section: Discussionsupporting
confidence: 75%
“…The interactions between Spartina anglica and Puccinella maritima were facilitative in low nutrient conditions, but not in high nutrient conditions [4]. The ericoid species Calluna vulgaris and Vaccinium oxycoccus were stronger competitors than the graminoid species Eriophorum vaginatum and Rhynchospora alba at high nutrient levels in peat bogs, but not at low nutrient conditions [18].…”
Section: Introductionmentioning
confidence: 97%
“…Apart from having better access to atmospheric nutrients, ericoids could also be better competitors than graminoids in peatlands (Ward and others 2009). In a competition experiment where the species had equal access to the supplied nutrients, two dwarf shrub species were better competitors than two cooccurring graminoid species at increasing N and P supply (Kool and Heijmans 2009). Phosphorus also seems to play an important role.…”
Section: Response Of Vascular Plantsmentioning
confidence: 98%